Radioactivity and Space Range of Ultra-Low-Activity for in vivo Off-line PET Verification of Proton and Carbon Ion Beam—A Phantom Study - Zhang, Fuquan; Zhang, Junyu; Lu, Yan; Sheng, Yixiangzi; Sun, Yun; Zhang, Jiangang; Cheng, Jingyi; Zhou, Rong (Frontiers in Public Health, 2021)
Purpose: The radioactivity induced by proton and heavy ion beam belongs to the ultra-low-activity (ULA). Therefore, the radioactivity and space range of commercial off-line positron emission tomography (PET) acquisition based on ULA should be evaluated accurately to guarantee the reliability of clinical verification. The purpose of this study is to quantify the radioactivity and space range of off-line PET acquisition by simulating the ULA triggered by proton and heavy ion beam. Methods: PET equipment validation phantom and low activity 18F-FDG were used to simulate the ULA with radioactivity of 11.1–1480 Bq/mL. The radioactivity of ULA was evaluated by comparing the radioactivity in the images with the values calculated from the decay function with a radioactivity error tolerance of 5%. The space range of ULA was evaluated by comparing the width of the R50 analyzed activity distribution curve with the actual width of the container with a space range error tolerance of 4 mm. Results: When radioactivity of ULA was >148 Bq/mL, the radioactivity error was <5%. When radioactivity of ULA was >30 Bq/mL, the space range error was below 4 mm. Conclusions: Off-line PET can be used to quantify the radioactivity of proton and heavy ion beam when the ULA exceeds 148 Bq/mL, both in radioactivity and in space range.